Stability of anti‐A blood group titers among blood group B renal transplant candidates. Issue 12 (28th September 2018) - Jacob, Reuben P.; Dean, Christina L.; Krummey, Scott M.; Goodman, Abigail L.; Roback, John D.; Gebel, Howard M.; Bray, Robert A.; Sullivan, Harold C.
Abstract : BACKGROUND: As deceased donor kidney allocation is based in part on blood type compatibility, group B candidates are disadvantaged due to their disproportionate representation on the wait list compared to the group B donor pool. To mitigate this discrepancy, group B candidates can receive group A2 or A2 B donor kidneys if their anti‐A titers are below a predetermined cutoff. Currently, eligibility is reverified quarterly to UNet based on individual center protocols, which can vary due to a lack of set guidelines for monitoring ABO titers in these patients. Our goal was to assess the stability of anti‐A titers in blood group B renal transplant candidates over time to provide data that could aid in the development of standardized ABO titer protocols. STUDY DESIGN AND METHODS: Titers performed between January 2011 and December 2015 were assessed for 191 group B patients with two or more documented titers. RESULTS: Fifty patients (26%) were ineligible, as the first titer exceeded the cutoff of 8. Of the remaining 141 patients, 19 (13%) became ineligible as the second titer exceeded 8. Thirty‐nine patients (28%) had no change in titer between samples, while 71 (50%) had a titer change that never exceeded 8. Only 12 patients (8.5% of total) experienced a titer change that affected eligibility after the second test. CONCLUSION: Although patients experience some variability in anti‐A titers over time, in most cases, stability did not affect candidate eligibility. Our results indicate that regular testing beyond the second titer may be unnecessary and represent test overutilization.